PERAN PEDAGANG KAKI LIMA (PKL) DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA (Studi di Kawasan Objek Wisata Pantai Mutiara Desa Gumanano Kecamatan Mawasangka Kabupaten Buton Tengah) - Nazrin, Nazrin; Bauto, La Ode Monto; Yusuf, Bakri (WELL-BEING: Journal of Social Welfare, 2021)
This research aims to determine the role and constraints of street vendors in improving family welfare in the Pantai Mutiara tourist attraction area, Gumanano Village, Mawasangka District, Central Buton Regency. This type of research is qualitative research. Data collection techniques were carried out by means of observation, interviews and documentation with 9 main informants of street vendors (PKL) in the Pantai Mutiara Tourism Object, Gumanano Village, Mawasangka District, Central Buton Regency and 5 people as supporting informants. The results showed that first, the role of street vendors (PKL) in improving family welfare in the Pantai Mutiara tourist area, namely increasing family income in meeting the needs of food, clothing, shelter, health, and educational needs. The two obstacles faced by street vendors in improving family welfare are physical capital, knowledge and skills.